\[\boxed{\text{867\ (867).\ }\text{Еуроки\ -\ ДЗ\ без\ мороки}}\]
\[1)\ A\ ( - 1;\ - 6):\ \]
\[8 \cdot ( - 1) - 14 = - 8 - 14 =\]
\[= - 22 \Longrightarrow не\ принадлежит;\]
\[2)\ B\ (2;2):\ \]
\[8 \cdot 2 - 14 = 16 - 14 =\]
\[= 2 \Longrightarrow принадлежит.\text{\ \ \ }\]
\[\boxed{\text{867.\ }\text{Еуроки\ -\ ДЗ\ без\ мороки}}\]
\[1)\ (a + 2)^{3} - 25 \cdot (a + 2) =\]
\[= (a + 2)(a + 7)(a - 3)\]
\[(a + 2)^{3} - 25 \cdot (a + 2) =\]
\[= (a + 2)\left( (a + 2)^{2} - 25 \right) =\]
\[= (a + 2)(a + 2 - 5)(a + 2 + 5) =\]
\[= (a + 2)(a - 3)(a + 7)\]
\[(a + 2)(a - 3)(a + 7) =\]
\[= (a + 2)(a - 3)(a + 7) \Longrightarrow\]
\[\Longrightarrow тождество\ верно.\]
\[2)\ a² + 2ab + b² - c^{2} + 2cd - d^{2} =\]
\[= (a + b + c - d)(a + b - c + d)\]
\[a^{2} + 2ab + b^{2} - c^{2} + 2cd - d^{2} =\]
\[= (a + b)^{2} - (c - d)^{2} =\]
\[= (a + b - c + d)(a + b + c - d)\]
\[(a + b - c + d)(a + b + c - d) =\]
\[= (a + b - c + d)(a + b + c - d) \Longrightarrow\]
\[\Longrightarrow тождество\ верно.\]